Rapid and scalable lubrication and replenishment of liquid-infused materials. Issue 2 (June 2016) - Damle, Viraj G.; Uppal, Aastha; Sun, Xiaoda; Burgin, Timothy P.; Rykaczewski, Konrad
Abstract : Liquid-infused surfaces (LIS) consist of a porous or textured solid matrix infused with a lubricating liquid. The presence of a thin film of the lubricant on the exterior surface facilitates dramatically the shedding of a wide range of liquids and solids, making LIS potential candidates for a variety of applications. However, before LIS can transition into industrial use, durability issues posed by lubricant depletion need to be addressed. In this paper an 'inside-out-in' system is introduced for rapid lubrication or relubrication of polymeric LIS. The system consists of an embedded millichannel liquid distribution network connected to the exterior polymer surface using periodically spaced vias and could be used to, for example, lubricate LIS-based personal protective gear. By using periodic contact angle measurements and spray impingement experiments, the authors show that release of a lubricant using this system leads to diminishing contact angle hysteresis of the exterior LIS surface nearly instantaneously. The proposed inside-out-in lubricant dispensing approach is a generic system that provides a rapid and scalable route to refresh the wetting properties of LIS consisting of any polymer–lubricant pair, which could facilitate transition of these materials into industrial use.